The stakeholder balance sheet : profiting from really understanding your market - Suntook, Farrokh; Murphy, John A., 1948- (Chichester, England ; Hoboken, NJ : Wiley, 2008)
This book provides an as yet unavailable tool, the Stakeholder Balance Sheet, enablingmanagers within any organisation to unlock the DNA of the market place in which they operate and to measure their effectiveness in understanding their markets and all the key stakeholders operating within them. This simple tool provides self-testing checklists at the end of each chapter that enables managers to look at stakeholder-sensitive issues in the same way that they might scrutinise financial statements (hence it will not seem alien to most managers).
The 9 point plan for sustaining and growing your market profitably -- In the beginning was--segmentation! -- Delving into the mind of the market : understanding the real stakeholder drivers -- From customer satisfaction and branding to loyalty and attraction -- Decision-making dynamics -- Staff motivation and perceptions -- Who else should be on your radar screen : the role and motivation of other external stakeholders and influencers -- Communicate (and communicate and communicate-- ) -- Constant renewal : searching for winning new product of service propositions -- An ongoing process : monitoring your performance -- Conclusion : the 9 point plan revisited.
Includes bibliographical references (pages 293-297) and index.
Print version record.
English.
John Wiley and Sons
Keywords: Stockholders; Corporations -- Investor relations; BUSINESS & ECONOMICS -- Investments & Securities -- General; Corporations -- Investor relations; Stockholders; Aandeelhouderswaarde; Organisatieonderzoek; Balanced scorecard